Efek Penyimpanan Semen Beku Terhadap Kualitas Spermatozoa Sapi Simental Pada Suhu 5°C - Hoesni, Fachroerozi; Adisetiawan, R.; Farizal, Farizal; Firmansyah, Firmansyah (Universitas Batanghari Jambi, 2024)
This study aimed to determine the effect of frozen semen storage on sperm quality. quality of Simmental cattle spermatozoa at 5° C. This research was conducted laboratory at the UPTD Laboratory of the Livestock Breeding Center of the Jambi Provincial Food Crops Horticulture and Livestock of Jambi Province, from July 10 to August 22, 2023. August 22, 2023. Completely Randomized Design (CRD) was used in the study. with 5 treatments and 5 replications so there were 25 experimental units. Treatment PO (control) = direct thawing, P1 = storage for 15 minutes, P2 = storage for 30 minutes. storage for 30 minutes. P3 = storage for 45 minutes, P4 = storage for 60 minutes. storage for 60 minutes. The variables observed were spermatozoa motility, spermatozoa viability, spermatozoa abnormality. The results of analysis of variance showed that the storage of frozen semen of Simmental cattle at 5 ° C with different times had a significant effect (P <0.05) on the motility of spermatozoa and spermatozoa viability and not significantly different (P>0.05) on spermatozoa abnormality. Based on the research results obtained It is concluded that storage of frozen semen inside at 5 ° C can maintain the quality of frozen semen of Simental cattle with a storage time of 45 minutes.